2018
DOI: 10.1021/acs.orglett.8b01931
|View full text |Cite
|
Sign up to set email alerts
|

Iron Porphyrin Catalyzed Insertion Reaction of N-Tosylhydrazone-Derived Carbenes into X–H (X = Si, Sn, Ge) Bonds

Abstract: An efficient Fe(TPP)Cl catalyzed insertion reaction of in situ generated benzylic carbenes from N-tosylhydrazones into X-H (X = Si, Sn, Ge) was developed. Silanes bearing tertiary, secondary, and primary (3°, 2°, and 1°) Si-H bonds all reacted well to afford insertion products in moderate to high yields (up to 97%), and the reaction time could be significantly shortened to 1 h under microwave irradiation. A programmable stepwise double insertion strategy was developed for the synthesis of unsymmetrical tetrasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
1
29
0
1
Order By: Relevance
“…Alternatively, GLY conversion by electrochemical oxidation has recently attracted much attention. [9][10][11][12][13][14][15][16] Electro-oxidation of GLY is a totally green process, which does not involve any toxic oxidants. More importantly, this method affords a facile route to achieve a high selectivity towards certain target compounds by optimizing catalyst structures and experimental conditions (e. g., applied potential, electrolyte pH and temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, GLY conversion by electrochemical oxidation has recently attracted much attention. [9][10][11][12][13][14][15][16] Electro-oxidation of GLY is a totally green process, which does not involve any toxic oxidants. More importantly, this method affords a facile route to achieve a high selectivity towards certain target compounds by optimizing catalyst structures and experimental conditions (e. g., applied potential, electrolyte pH and temperature).…”
Section: Introductionmentioning
confidence: 99%
“…[26] Moreover, graphene/P4VP composites have been used in pH sensors [27] and as catalysts for glycerol oxidation. [28] These results suggest that P4VP would be an excellent matrix material for synthesizing GNRs. Here, we report the synthesis of GNRs in acetone and P4VP using the laser ablation in liquid (LAL) technique (Figure 1a).…”
Section: Introductionmentioning
confidence: 91%
“…It has been reported that 1,3-dicarbonyl compounds could be applied as alkyl radical precursors under the oxidative conditions, which further added to C=C bond furnish C-C bond formation products. [59][60][61] In 2018, our group reported a convenient radical cascade cyclization of 2-(allyloxy)arylaldehydes 47 with 1,3-dicarbonyl compounds 48 to synthesize 1,5-/1,3-dicarbonyl-containing chroman-4-ones 49 in the presence of AgNO 3 /K 2 S 2 O 8 under mild reaction conditions (Scheme 10). [62] The obtained 1,5-/1,3-dicarbonyl-containing chroman-4-ones 49 could further be used in subsequent transformations.…”
Section: Silver-promoted Reactionsmentioning
confidence: 99%